Comparative proteomic analysis of insulin receptor isoform A and B signaling. (1st November 2022) - Malaguarnera, Roberta; Gabriele, Caterina; Santamaria, Gianluca; Giuliano, Marika; Vella, Veronica; Massimino, Michele; Vigneri, Paolo; Cuda, Giovanni; Gaspari, Marco; Belfiore, Antonino
Abstract: The insulin receptor (IR) gene undergoes differential splicing generating two IR isoforms, IR-A and IR-B. The roles of IR-A in cancer and of IR-B in metabolic regulation are well known but the molecular mechanisms responsible for their different biological effects are poorly understood. We aimed to identify different or similar protein substrates and signaling linked to each IR isoforms. We employed mouse fibroblasts lacking IGF1R gene and expressing exclusively either IR-A or IR-B. By proteomic analysis a total of 2530 proteins were identified and quantified. Proteins and pathways mostly associated with insulin-activated IR-A were involved in cancer, stemness and interferon signaling. Instead, proteins and pathways associated with insulin-stimulated IR-B-expressing cells were mostly involved in metabolic or tumor suppressive functions. These results show that IR-A and IR-B recruit partially different multiprotein complexes in response to insulin, suggesting partially different functions of IR isoforms in physiology and in disease. Graphical abstract: Image 1 Highlights: IR-A and IR-B recruit different multiprotein complexes in response to insulin. Several enriched proteins/pathways associated with activated IR-A are involved in cancer. Insulin-activated IR-B exhibits a proteomic profile enriched mainly in proteins with metabolic functions. Both IR isoforms but especially IR-A recruit proteins involved in innate immunity.